Osteochondral Allograft Transplantation and Opening Wedge Tibial Osteotomy: Clinical Results of a Combined Single Procedure. (July 2018) - Hsu, Albert C.; Tirico, Luis E. P.; Lin, Abraham G.; Pulido, Pamela A.; Bugbee, William D.
Objective: To evaluate the outcome of patients who have undergone simultaneous osteotomy and osteochondral allograft (OCA) transplantation. Our hypothesis is that use of high tibial osteotomy and fresh OCA in a combined procedure is safe and effective without increasing morbidity in comparison to OCA alone. Design: A case series of 17 patients underwent tibial osteotomy and simultaneous OCA during a single surgery. Osteotomy was indicated when axial alignment was within the affected compartment. Patients had a minimum of 2 years of follow-up after surgery. The mean graft size was 8.7 cm 2, with 82% located on the medial femoral condyle alone and 18% involving the medial femoral condyle and one or more other sites. Data collection included demographics, osteotomy correction, graft site(s) and area, and clinical evaluation. Failure was defined as conversion to arthroplasty. Results: Two of 17 patients (12%) failed at a mean of 9.3 years. The remaining 15 patients (88%) had intact allografts with mean survival of 8.1 years (SD 3.3). Five patients (29%) had an additional procedure, all undergoing osteotomy hardware removal. Of those with surviving allografts, mean pain and function scores improved significantly from the preoperative to postoperative assessment and International Knee Documentation Committee total scores improved significantly from 40.9 ± 15.4 preoperative to 75.5 ± 24.0 at latest follow-up ( P = 0.003); 92% of patients were satisfied with the results of the surgery. No postoperative complications occurred. Conclusion: Combining high tibial osteotomy and OCA in properly selected patients is safe and effective.